2016
DOI: 10.1016/j.cell.2016.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Domestication and Divergence of Saccharomyces cerevisiae Beer Yeasts

Abstract: SummaryWhereas domestication of livestock, pets, and crops is well documented, it is still unclear to what extent microbes associated with the production of food have also undergone human selection and where the plethora of industrial strains originates from. Here, we present the genomes and phenomes of 157 industrial Saccharomyces cerevisiae yeasts. Our analyses reveal that today’s industrial yeasts can be divided into five sublineages that are genetically and phenotypically separated from wild strains and or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

50
874
2
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 585 publications
(976 citation statements)
references
References 72 publications
50
874
2
5
Order By: Relevance
“…Both genes have been shown to be involved in detoxifi-cation of phenylacrylic acids (15,16). Recent genetic analyses have revealed that PAD1 and FDC1 genes are interrupted by nonsense mutations in many industrial yeast strains (17). Our findings demonstrate that the functionality of AroY-C iso or Fdc1 is dependent on the presence of an intact copy of PAD1 or coexpression of aroY-B, thereby providing evidence that AroY-B is functionally equivalent to Pad1.…”
supporting
confidence: 48%
See 1 more Smart Citation
“…Both genes have been shown to be involved in detoxifi-cation of phenylacrylic acids (15,16). Recent genetic analyses have revealed that PAD1 and FDC1 genes are interrupted by nonsense mutations in many industrial yeast strains (17). Our findings demonstrate that the functionality of AroY-C iso or Fdc1 is dependent on the presence of an intact copy of PAD1 or coexpression of aroY-B, thereby providing evidence that AroY-B is functionally equivalent to Pad1.…”
supporting
confidence: 48%
“…The product formed by decarboxylation of ferulic acid, 4-vinylguaiacol, is a compound with smokelike characteristics that is considered an off-flavor in most beers and wines. For this reason, many loss-of-function mutations were acquired in PAD1 or FDC1 in strains used for wine or beer production during their domestication (17,25). In a variety of other yeast species (e.g., Kluyveromyces marxianus or Yarrowia lipolytica), no Pad1 homologues can be found and, consistently, these species are not able to decarboxylate phenylacrylic acids (26).…”
Section: Discussionmentioning
confidence: 99%
“…High quality sequencing, de-novo assembly, and extensive phenotyping of 157 S. cerevisiae strains used for industrial production of beer and other fermented beverages (in their natural ploidy) have revealed that industrial yeast are genetically and phenotypically distinct from wild strains [27]. On this basis, there are many genetic approaches to the design of a superior yeast that can ferment and provide a particular style of beer.…”
Section: Genetic Improvement Of Brewing Strainsmentioning
confidence: 99%
“…By using microsatellite markers, Legras et al [4] gave the first indication that wine and ale beer strains were genetically distinct. Gallone et al [5] and Gonçalves et al [6] investigated a wide collection of ale-type beer yeasts using complete genome sequences and showed that they were distinct from other industrially relevant strains of S. cerevisiae. Ale-type strains were grouped in a main cluster that included various types of German, British, Belgian, and American beer strains.…”
Section: Ale Yeastsmentioning
confidence: 99%
“…Those authors also showed that beer yeasts have a high incidence of polyploidy and aneuploidy and, probably as a consequence of this, limited or no sporulation ability. Genome analyses and large-scale phenotyping of industry-specific traits revealed that some traits have been selected during brewing yeast domestication, such as greater capacity to metabolize maltotriose [5] and reduced production of phenolic off flavours.…”
Section: Lager Yeastsmentioning
confidence: 99%